Color Stability of Flowable Composites in Different Viscosities - KORKUT, BORA (MARMARA UNIV, INST HEALTH SCIENCES, 2020)
Objective: This in vitro study was aimed to evaluate the color stability of resin-based composite materials in different viscosities immersed in various colorant solutions. Methods: 250 composite samples of A2 shades were prepared using two high-viscosity flowable composites (G-aenial Injectable, GC, Tokyo, Japan; Estelite Super Low Flow, Tokuyama Dental, Japan A2 shade), a bulk-fill flowable composite (Filtek Bulk-Fill, 3M, USA), a low-viscosity flowable composite (Filtek Ultimate Flowable, 3M, USA), and a packable composite (Filtek Ultimate, 3M, USA). Samples were polymerized and polished from both sides with a LED curing unit (Valo Grand, Ultradent, Switzerland) and polishing discs (SofLex, 3M, USA). Then divided by test groups (n=10 for each) regarding colorant solutions; coke (CocaCola Company, USA), tea (Yellow Label, Lipton, Rize, Turkey), coffee (Nescafe Classic; Nestle, Switzerland), red wine (Doluca, OkuzgOzu, Doluca, Istanbul, Turkey), and physiologic saline as the control solution. Samples were discolored for 144 hours with solutions in an incubator at 37 degrees C, and repolished after discoloration. Color measurements were performed using a clinical spectrophotometer (EasyShade IV, Vita, Germany) and a colorimeter (ShadeStar, Dentsply Sirona, USA). Two-way Anova test and Tukey HSD test were used for statistical analyses. Results: Composite material and colorant solution were considered effective factors for influencing the color change, regarding after discoloration scores (p<0.001, p<0.001, respectively). In addition, colorant solution was found more effective than the type of composite. Filtek Ultimate Flowable presented significantly the highest level of color change among others (p<0.001), for both 'after discoloration (5,34 +/- 3,78b)' and 'after repolishing (3,93 +/- 2,23b)' periods. No significant difference in color change was found between Gaenial Injectable, Estelite Super Low Flow, Filtek Bulk Fill Flowable, and Filtek Ultimate, and all showed imperceptible color changes (Delta E*<3.7). Red wine solution showed significantly the highest level of color change (8,00 +/- 2,08d) among other colorant solutions (p<0.001), and followed by coffee (4,59 +/- 1,52c), tea (3,38 +/- 1,21b), and coke (1,58 +/- 0,99a), respectively. A strong relation was found between the spectrophotometer and colorimeter measurements. Conclusion: Viscosity was considered an effective factor for discoloration of RBCs. Color stability of high viscosity flowable composite materials were found to be good and similar to packable composite. Samples immersed in red wine showed the greatest level of discoloration and followed by coffee, tea, and coke. The repolishing procedure was considered effective for reversing back the surface discoloration of composite materials.
Keywords: Discoloration; repolishing; flowable composite; viscosity; color stability; RESIN-BASED COMPOSITES; SURFACE-ROUGHNESS; STAINING SUSCEPTIBILITY; POLYMERIZATION; NANOTECHNOLOGY